Under-dome transitions in the churches of the Bagratid era, 9th–11th centuries - Kazaryan, Armen (project baikal, 2025)
The article traces the preferences of the architects of Ani and the regions of the Christian East closest to the Armenian Bagratid kingdom in relation to the choice of the type of under-dome transition, as well as the ability of the craftsmen to interpret their forms in a variety of ways, which were generally established in the Armenian architecture of the 7th century. Using examples of outstanding works of the epoch, the transitions of three types and intermediate variants are consistently analyzed.
Keywords: Armenian architecture; Eastern Christian church; under- dome transition; pendentives; squinches; squinch-pendentive transition